The effect of acellular dermal matrix therapy on biphasic calsium sulfate bone graft - Angga Febriharta; Kwartarini Murdiastuti (Majalah Kedokteran Gigi Indonesia, 2020)
Infrabony pocket therapy is needed to eliminate pocket wall, creating easy to clean conditions for new attachment, and bone regeneration. Biphasic calcium sulfate (BCS) bone grafts combined with collagen membranes are known to regenerate bone tissue and have good osteoconductive effects. The addition of collagen membranes promotes migration and proliferation of fibroblast cells, osteoblasts, and homeostasis. However, the collagen membrane is a rapidbioresynthesis and may cause disease transmission from animal. Acellular dermal matrix (ADMA) membrane contains a bioactive matrix that has the ability to support normal revascularization, cell repopulation, and tissue remodeling. Combination of BCS with ADMA membrane are proven to induce bone and tissue regeneration. The objective of this study is to determine the therapeutic effect of BSC and ADMA combination to eradicate pocket, gingival recession, bone recession and attachment loss. The samples were taken from 20 infrabony pocket sites divided into 2 groups. The first was treated by combination of BCS and ADMA, while the second group was treated by the combination of BCS and collagen membrane. After 1 and 3 months of flap surgery, the result was observed by probing depth(PD), relative attachment loss (RAL), gingival recession, alveolar bone height and radiological examination. The result showed the decrease of PD, RAL, gingival recession, and alveolar bone height in both two groups. However, there wereno significant differences between those two groups. In conclusion, the combination of BCS and ADMA or BCS and collagen decreased the PD, RAL, gingival recession and alveolar bone height.